2017
DOI: 10.1016/j.ebiom.2017.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Homeostasis Disruption in a Novel Frontotemporal Dementia Mouse Model Expressing Cytoplasmic Fused in Sarcoma

Abstract: Cytoplasmic aggregation of fused in sarcoma (FUS) is detected in brain regions affected by amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD), which compose the disease spectrum, FUS proteinopathy. To understand the pathomechanism of ALS-FTD-associated FUS, we examined the behavior and cellular properties of an ALS mouse model overexpressing FUS with nuclear localization signal deletion. Mutant FUS transgenic mice showed hyperactivity, social interactional deficits, and impaired fear memory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 46 publications
6
26
0
Order By: Relevance
“…Certain mouse lines that display altered social engagement, reduced anxiety, hyperactivity and memory impairments are regarded as models of FTD. These include GRN knockout mice and transgenic mice expressing mutant tau, TDP‐43 lacking the nuclear localisation signal and FUS with a C‐terminal shorter than in our mice . Overall, behavioural abnormalities observed in L‐FUS[1‐359] mice are consistent with those reported for these mouse models.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Certain mouse lines that display altered social engagement, reduced anxiety, hyperactivity and memory impairments are regarded as models of FTD. These include GRN knockout mice and transgenic mice expressing mutant tau, TDP‐43 lacking the nuclear localisation signal and FUS with a C‐terminal shorter than in our mice . Overall, behavioural abnormalities observed in L‐FUS[1‐359] mice are consistent with those reported for these mouse models.…”
Section: Discussionsupporting
confidence: 83%
“…These include GRN knockout mice and transgenic mice expressing mutant tau, TDP-43 lacking the nuclear localisation signal and FUS with a C-terminal shorter than in our mice. [30][31][32][33] Overall, behavioural abnormalities observed in L-FUS[1-359] mice are consistent with those reported for these mouse models.…”
Section: Immunohistochemistrysupporting
confidence: 83%
“…Several studies have demonstrated that many RBPs with known mutations associated with ALS/FTD accumulate in the cytoplasm of the affected regions of the central nervous system and possibly contribute to the RNA dysregulation implicated in ALS/FTD pathogenesis [3][4][5][6]11 . Our previous study showed that the cytoplasmic mutant FUS aggregates observed in the ΔNLS-FUS Tg mice sequester mRNA and RNA transporters, leading to a disturbance in RNA/protein homeostasis in the dendrites, even before neuronal loss occurs 8,9 . Our current study provides valuable insights regarding the RNA dysregulation associated with the early stages of ALS/FTD before neuronal loss.…”
Section: Discussionmentioning
confidence: 99%
“…We recently generated a transgenic (Tg) mouse model for ALS/FTD overexpressing the exogenous nuclear localization signal deletion mutant of human fused in sarcoma (ΔNLS-FUS), reflecting juvenile ALS 8,9 . The ΔNLS-FUS Tg mice show behavioral phenotypes such as cognitive deficits associated with FTD by nine weeks of age and show significant progressive motor impairment by five month of age, indicating that this Tg mouse line can be used as a model for ALS/FTD 8,9 . Histological and cytological studies of this Tg mouse model indicated that cytoplasmic FUS aggregates sequester mRNA and RNA transporters leading to synaptic and dendritic spine dysfunction resulting in FTD-like phenotypes even before the appearance of neuronal loss.…”
mentioning
confidence: 99%
“…Hyperactivity and social and executive dysfunctions have been previously documented in other mouse models of ALS/FTD. It is noteworthy for instance that transgenic overexpression of mutant FUS leads to hyperactivity and cognitive deficits 63 . Similar abnormalities are also observed in TDP-43 knock-in mice 64 , C9ORF72 BAC transgenic mice 65 or Chmp2b transgenic mice 66 , suggesting that ALS mutations commonly lead to various behavioral alterations in mouse models, that are dominant over motor dysfunction.…”
Section: Discussionmentioning
confidence: 99%